Strengthening mathematical skills in future teachers through service-learning in a liquid society - Gómezescobar, Ariadna; López-Iñesta, Emilia; Sanz, Maria T.; Santágueda-Villanueva, María (LUMAT: International Journal on Math, Science and Technology Education, 2026)
This study presents “Aula de Apoyo”, a Service-Learning programme in which undergraduate education students provide extracurricular mathematics support to low-achieving Primary learners, particularly those from disadvantaged backgrounds. By applying knowledge from Mathematics Didactics, undergraduates strengthen their teaching skills while helping to reduce educational gaps. A mixed-methods design was used with eight tutor–student pairs. Tutors evaluated their training positively, highlighting the usefulness of the Concrete–Pictorial–Abstract approach, increased responsibility, and the desire for a longer intervention. The findings indicate that Service-Learning supports subject-matter understanding, fosters social engagement, and develops key transversal skills such as empathy and adaptability, thereby contributing to more equitable learning opportunities and aligning with European Higher Education priorities. This study adds to an underexplored line of research by integrating structured extracurricular mathematics support within a Service-Learning framework in initial teacher education. Moreover, the programme helps prepare future teachers to face the challenges of a rapidly changing liquid society, where adaptability and social responsibility are increasingly essential.